Dark energy - Wang, Yun, 1964- (Weinheim : Wiley-VCH, 2010)
"Dark energy research aims to illuminate the mystery of the observed cosmic acceleration, one of the fundamental problems in physics and astronomy today. This book presents a systematic and detailed review of the current state of dark energy research, with the focus on the examination of the major observational techniques for probing dark energy. It can be used as a textbook to train students and others who wish to enter this extremely active field in cosmology."-- p. 4 of cover.
The dark energy problem -- The basic theoretical framework -- Models to explain cosmic acceleration -- Observational method I : type Ia supernovae as dark energy probe -- Observational method II : galaxy redshift surveys as dark energy probe -- Observational method III : weak lensing as dark energy probe -- Observational method IV : clusters as dark energy probe -- Other observational methods for probing dark energy -- Basic instrumentation for dark energy experiments -- Future prospects for probing dark energy.
0
Includes bibliographical references (p. 229-237) and index.
Keywords: Dark energy (Astronomy); Weltall; Expansion; Dunkle Energie